2021
DOI: 10.1364/boe.433427
|View full text |Cite
|
Sign up to set email alerts
|

Compressed sensing time-resolved spectrometer for quantification of light absorbers in turbid media

Abstract: Time-resolved (TR) spectroscopy is well-suited to address the challenges of quantifying light absorbers in highly scattering media such as living tissue; however, current TR spectrometers are either based on expensive array detectors or rely on wavelength scanning. Here, we introduce a TR spectrometer architecture based on compressed sensing (CS) and time-correlated single-photon counting. Using both CS and basis scanning, we demonstrate that—in homogeneous and two-layer tissue-mimicking phantoms made of Intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 69 publications
1
12
0
Order By: Relevance
“…The spectral resolution of the modified TR spectrometer-determined as the FWHM of the lamp's narrowest peak-was 5.8 nm; this was an improvement from the 6.1 nm resolution of the original spectrometer. 10 Figure 4C compares IRFs at 750 nm acquired by the original TR spectrometer 10 -which used a PMT detectorand the modified TR spectrometer; as expected, use of a hybrid detector eliminated the afterpulsing observed with the PMT.…”
Section: System Characterizationsupporting
confidence: 55%
See 3 more Smart Citations
“…The spectral resolution of the modified TR spectrometer-determined as the FWHM of the lamp's narrowest peak-was 5.8 nm; this was an improvement from the 6.1 nm resolution of the original spectrometer. 10 Figure 4C compares IRFs at 750 nm acquired by the original TR spectrometer 10 -which used a PMT detectorand the modified TR spectrometer; as expected, use of a hybrid detector eliminated the afterpulsing observed with the PMT.…”
Section: System Characterizationsupporting
confidence: 55%
“…We suspect that this causes the decrease in SSIM index, as a reduction in signal would impact the SNR of compressed data less due to the inherent suppression of highfrequency noise. 10 However, on average, SSIM index remains high, staying above 0.85 throughout the experiment. Given the small proportion of affected wavelengths, the impact of this effect on chromophore recovery is likely minimal.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…When analyzing trNIRS measurements, the IRF can be easily measured and its effects accounted for by convolving it with the analytical model. Note that for hyperspectral trNIRS measurements, the IRF of each wavelength must be measured as it has been shown that both the shape and temporal position of the IRF change with wavelength ( Ioussoufovitch et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%